Corporate image and the police service: an examination of Durham constabulary - Parker, Anthony F. (1995)
The concept of corporate image has only relatively recently moved from the pages of design magazines to managerial, cultural and organisational texts. The purpose of this research and subsequent thesis is to make a contribution to the knowledge of the concept of corporate image and in particular to establish any relevance to the arguably unique context of the police service. A review of literature identified that there had been little, if any, academic research on corporate image; although some work of a descriptive and commercial nature was available on the design perspective of the subject. Furthermore, the impact or influence of corporate culture on the corporate image projected by organisations had not been explored. The methodology of focus group research, using psychological predictive techniques, enabled a holistic, exploratory approach which was necessary due to the lack of theoretical underpinning of corporate image and the apparent interdisciplinary nature of the concept. The research establishes links between culture and the formation of corporate image. It then looks specifically at the culture of Durham Constabulary and its effect on the corporate image of the organisation. The thesis shows that corporate image uses old concepts with new terminology. The term does, however, offer advantages in facilitating the management of several key influences on organisational effectiveness. Finally, it is argued that a corporate image programme could have importance for Durham Constabulary